IMPROVING STUDENTS' VOCABULARY USING CARD GAME (AN ACTION RESEARCH AT THE FIFTH YEAR OF SD NEGERI SEDAYU I SLOGOHIMO) - SURYANI , IIN (2010)
The research aims at describing the implementation of teaching vocabulary using card game. The result of this research is expected to give contribution to the teaching - learning English in elementary school. The study was implemented in SD Negeri I Sedayu, Slogohimo, Wonogiri using classroom action research. The writer took the fifth year students as the subject of research. The object of research was improving students vocabulary using card game. The writer compared the result of pre-test and three post-test to collect the required data and the counted the improvement score. To ensure that vocabulary can improve the students vocabulary the result in post-test should show significant improvement from the result of pre-test. The results of the research show that (1) in the first cycle the average result of pre - test is 3,85 (poor), in the post - test 1 the result increases to 6,19 (low) (2) in the post - test 2 the result increases to 6,76 (fair) than the last post - test 3 the result increases to 8,04 (good). Considering the result of the research, there is improvement on the student's mastery of vocabulary from the first and second cycle. It can be concluded that card game can be implemented to improve students vocabulary.